The role of ethylene in the development of plant form - Dolan, L (1997)
Ethylene is a gaseous growth factor involved in a diverse array of cellular, developmental and stressrelated processes in plants. A number of examples of the role played by ethylene in the development of form in plants are described; reaction wood formation, floral induction, sex determination, flooding-induced shoot elongation, and leaf abscission. Recent advances in the understanding of the molecular mechanism underpinning post-pollination perianth wilting in orchids is reviewed. This study indicates that the process of post-pollination perianth wilting involves an early increase in sensitivity to endogenous levels of ethylene which set in motion a chain of events in which ethylene autocatalytically induces its own synthesis in the pistil. Ethylene also induces the expression of ACO in the perianth which converts pistil-derived ACC into ethylene which drives the wilting process. Concepts drawn from this system are then applied to the Arabidopsis root epidermis in which ethylene is a positive regulator of root hair development in an effort to come to a mechanistic understanding of the process of pattern formation in this system. Understanding the molecular basis of the role of ethylene in these model systems will provide useful paradigms for examining the part played by ethylene in the diverse array of processes in which this growth factor is involved.